Widening the circle of leadership : strenghtening conservation NGOs in the Eastern Caribbean - Towle, Judith A. (Island Resources Foundation WashingtonUS, 1995)
Presents Island Resources Foundation's experiences and findings following almost a decade of focused assistance to conservation non-governmental organisations in the Eastern Caribbean.